On some problems arising from the application - Zelenyak, T.I. (Нелинейные граничные задачи, 1999)
We consider some mathematical problems, arising from the study of the continuous media. It is characteristic that these evolutionary problems are described by the equations, which do not belong to the systems of the Cauchy-Kovalevskaja class.